Development and prospect of sidelink technology - Boyuan ZHANG; Xueyan HUANG; Zhenshan ZHAO; Shichang ZHANG; Teng MA; Liang LIU (Dianxin kexue)
Sidelink technology has been widely used in V2X scenarios.The potential technical consideration for Rel-18 feature set will be given out, including the traditional enhancement orientation for traditional sidelink technology, such as carrier aggregation and sidelink-unlisence.The scenario extension for sidelink relay, such as UE to UE relay and multi-connection in relay scenario, the application of sidelink technology in accurate positioning scenario.In addition, how to combine sidelink technical with other latest technology was discussed, such as reflective intelligent surface (RIS) and blockchain technology, to solve its own shortage.